DISKURSUS CITRA TENTARA NASIONAL INDONESIA DALAM AKUN TWITTER @txtdrberseragam - Habibah, Ghassini Dea (Paradigma, 2023)
Every country has a defense for the sake of the security and sovereignty of the country. Indonesia itself has an Indonesian National Armed Forces (Tentara Nasional Indonesia) institution which was formed after independence to function as national defense. As the front guard in national defense, TNI has its own close relationship with the community. This study discusses the discourse on the image of the TNI that is present in social media, especially on Twitter on the @txtdrberseragam account. This study uses discourse analysis with Michel Foucault’s archaeological and geneaological analysis. This research is a literature review research using social media as a source of data collection. The results of this study show that the account @txtdrberseragam has succeeded in showing the image of the TNI in every uploaded discourse. In this study, it was found that the discourse regarding the image of the TNI that was present in the account was divided into four namely; the arrogance of TNI members, involvement of TNI members in criminal acts, image building of the members of TNI, and a shift in the meaning of the TNI institution